A D-Band Phased-Array Chain Based on a Tunable Branchline Coupler and a Digitally Controlled Vector Modulator - Jonathan Bott; Florian Vogelsang; Nils Pohl (IEEE Journal of Microwaves, 2024)
Wireless communication and sensing applications seek higher frequencies to enable higher data rates or more precise localization using a wider modulation bandwidth. Particularly, 6G and autonomous driving research projects focus on the D-band. With higher frequencies, antennas can be placed closer together, allowing for more antennas in the same area and creating a narrower beam. However, a greater number of channels increases system complexity. Each antenna typically requires one vector modulator in a phased-array system, which entails four analog control voltages and four DACs. Consequently, increasing the frequency and utilizing more channels can result in an enlarged system size due to the complex PCB design. This article presents a phased-array chain consisting of a tunable branchline coupler based on varactor diodes, a digital vector modulator, and a power amplifier. The combination of varactor diodes and the VM enables coarse phase changes through 4-bit digital switching and precise phase adjustment through varactor tuning. This approach demonstrates that a four-element array only requires two DACs instead of 16 to cover the entire angular range. The phased-array chain was designed and manufactured using B11HFC silicon-germanium technology from Infineon Technologies AG.